Principles of pharmacology : basic concepts & clinical applications - Munson, Paul L. (New York : Chapman and Hall, 1995)
Designed primarily as a consice reference book for medical and graduate students, residents, postdoctoral fellows, faculty members, and health professionals in medicine, pharmacy, dentistry, veterinary medicine, nursing, and public health.
SECTION 1: General Principles of Pharmacology -- SECTION II: Peripheral Neuropharmacology -- SECTION III: Central Neuropharmacology -- SECTION IV: Cardiovascular and Pulmonary Pharmacology -- SECTION V: Renal Pharmacology -- SECTION VI: Pharmacology of Hormones and Reproduction -- SECTION VII: Pharmacology of Nutrients and Nutritional Diseases -- SECTION VIII: Drugs Affecting Gastrointestinal Function -- SECTION IX: Drugs Affecting Blood, the Immune System and Inflammation -- SECTION X: Pharmacology of Skin -- SECTION XI: Chemotherapeutic Drugs -- SECTION XII: Natural Medicinal Products -- SECTION XIII: Elements of Toxicology -- SECTION XIV: Governmental Regulation of Drugs -- SECTION XV: Phormacology for Special Patient Populations
Includes bibliographical references and index.
Keywords: PHARMACOLOGY